(untitled) (Jurnal Mekanikal, 2019)
Electricity consumption in commercial buildings needs serious and particular attention due to current situation of increased world fuel prices. This paper presents the potential savings in order to achieve energy efficiency in academic building through optimization and operational strategies. This study also helps to identify the energy savings gap within the building through energy saving measures and application of renewable technologies. There are three main components that have been selected as the subjects of investigation, i..e., the cooling equipment, lighting and electrical appliances. A number of existing analytical tools such as ASHRAE CLTD/CLF, lumen method, net present value and benefit cost ratio have been adopted during the course of conducting this research. The results showed that the usage of air-conditioning, lighting and electrical appliances can be reduced by 12%, 52% and 40%, respectively when all the energy saving measures were in place and implemented.